Analisis Pengaruh Debt Maturity dan Cash Holding terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Variabel Intervening : Studi Kasus pada Perusahaan Subsektor Perbankan yang Terdaftar di Bursa Efek Indonesia pada Tahun 2020-2023 - Noara Amreta Eriawati; Ninik Anggraini; Srikalimah Srikalimah (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2025)
This study aims to examine and analyze the influence of debt maturity and cash holding on dividend policy, the effect of debt maturity and cash holdings on company value, and the effect of debt maturity and cash holdings on company value through dividend policies in banking sub-sector companies listed on the Indonesia Stock Exchange for the 2020-2023 period. The sampling technique uses the purposive sampling method. Secondary data was obtained from the annual financial statements. The data analysis method uses path analysis with two structural equations to test the direct and indirect influence of independent variables on dependent variables through intervening variables. The results of the structural equation 1 study show that debt maturity has no effect on dividend policy, and cash holdings have an effect on dividend policy. The results of structural equation 2 show that debt maturity affects the value of the company and cash holdings have no effect on the value of the company. The results of the testing of intervening variables show that dividend policy can mediate debt maturity to company value and dividend policy can mediate cash holdings to company value. The predictive ability of the two variables on the dividend policy was 13.6% and the remaining 12.6% was influenced by other variables outside the research model and the predictability of the three variables on the company's value was 15.7% and the remaining 14.7% was influenced by other variables outside the research model.